Angiopoietin-2 predicts all-cause mortality in male but not female end-stage kidney disease patients on hemodialysis - Chu, Chang; Chen, Xin; Hasan, Ahmed A; Szakallova, Angelika; Krämer, Bernhard; Tepel, Martin; Hocher, Berthold (Nephrology, dialysis, transplantation, 2022)
Angiopoietin-2 (Ang-2) plays a pivotal role in pathological vascular remodeling and angiogenesis. Both vascular mechanisms are active in patients with end-stage renal disease (ESRD) and may contribute to the high mortality in these patients. The aim of this multicenter prospective cohort study was to investigate baseline serum Ang-2 concentrations in ESRD patients on hemodialysis (HD) for their ability to predict all-cause mortality.We conducted a prospective cohort study in 340 stable HD patients from different chronic dialysis centers in Berlin, Germany. The primary endpoint was all-cause mortality during a 5-year follow-up period. Blood samples and clinical data were collected at baseline. Serum Ang-2 was measured with a validated enzyme-linked immunosorbent assay (Biomedica, Vienna, Austria).A total of 313 HD patients (206 men and 107 women) were finally included in the study. Receiver operating characteristic (ROC) analysis of Ang-2 concentrations yielded an area under the curve (AUC) of 0.65 (P < 0.0001) for predicting all-cause mortality in the entire study population and was used to determine the optimal cut-off (111.0 pmol/L) for all-cause mortality. Kaplan-Meier survival analysis indicated that male but not female end-stage kidney disease patients on HD with higher Ang-2 concentrations had a significantly lower survival (log-rank test, P < 0.0001 and P = 0.380 for male and female patients, respectively). Multivariable Cox regression analyses adjusted for age, comorbidity, smoking, dialysis vintage, serum creatinine, hemoglobin, C-reactive protein, serum albumin, intact parathyroid hormone (iPTH), low-density lipoprotein (LDL) and Kt/V likewise indicated that elevated Ang-2 concentrations are associated with all-cause mortality in male {hazard ratio [HR] 3.294 [95% confidence interval (CI) 1.768-6.138]; P = 0.0002} but not in female end-stage kidney disease patients on HD [HR 1.084 (95% CI 0.476-2.467); P = 0.847].Ang-2 at baseline is independently associated with all-cause mortality in male ESRD patients on HD.
Gesehen am 09.01.2024